Interior Design and its Impact on of Employees' Productivity in Telecom Sector, Pakistan - Akhtar, Naeem; Ali, Saqib; Salman, Muhammad; Rehman, Asad-Ur-; Ijaz, Aqsa (Journal of Asian Business Strategy, 2014)
Better interior design is compulsory to increase employees’ productivity in every sector either manufacturing or service. Five dimensions of interior design were used in this study like Furniture, Noise, Temperature, Lighting and Spatial arrangements. The major purpose of present study is to examine the relationship between office interior design and employees’ productivity. The present study is quantitative in nature. Data was collected from the employees of telecom sector of Sahiwal division in Punjab. A 200 sample size was selected to conduct this research. Primary data was collected by structured questionnaire. The Descriptive Statistics, Correlation and Regression analysis were used by SPSS to find out the impact of interior design on employees’ productivity. Results showed that interior design has positive association with employees’ productivity.